i would say that x = 4
* * * * *
I, on the contrary, would say that x = 4 or 0.
The equation is:
2x2 - 8x = 0;
and it factorises as:
2x(x - 4) = 0; whence,
x = 4 or 0.
Also, you can check your result:
2(0)2 = 0 = 8(0); and
2(4)2 = 32 = 8(4).
This shows that we must be doing something right.
To find the product of 8x and 2x, you multiply the coefficients (8 and 2) to get 16, and then multiply the variables (x and x) to get x^2. Therefore, 8x * 2x equals 16x^2.
2(x + 3)(x + 1)
x = 1/6
(2x + 4)(2x - 4) to check your answer, use the FOIL method (first, outside, inside, last) F.... 2x x 2x = 4x^2 0.... 2x x -4 = -8x I..... 2x x 4 = 8x L.... 4 x -4 = -16 so 4x^2 - 16 = (2x + 4)(2x - 4)
8x + 6 = 2x + 24 To solve, collect like terms on each side; collect the x's on the left, the numbers on the right: 8X + 6 = 2x + 24 8x - 2x = 24 - 6 6x = 18 6x / 6 = 18 / 6 x = 3
2x times 4x is 8x squared- then that times x is 8x to the power of three.Mathmatically represented as 8x^3
If: 6-2x = 8x Then: x = 3/5 or 0.6
y + x2 = 8x y = 2x Substitute from the second equation into the first: 2x + x2 = 8x Subtract 8x from both sides (and change order): x2 - 6x = 0 x(x - 6) = 0 So x = 0 which gives y = 0 or x = 6 which gives y = 12
8x = 2x + 15 6x = 15 x = 15/6 = 2.5
x=6.
x = 9.
x=5
x= -1
To solve the expression 8x^2 * 2x, you first multiply the coefficients (8 * 2 = 16). Then, you multiply the variables with the same base by adding their exponents (x^2 * x = x^(2+1) = x^3). Therefore, the simplified expression is 16x^3.
To find the product of 8x and 2x, you multiply the coefficients (8 and 2) to get 16, and then multiply the variables (x and x) to get x^2. Therefore, 8x * 2x equals 16x^2.
x squared -2x-3 equals 0 is the same as (x + 1)(x - 3) = 0
8x + 16 = 6x -> 2x + 16 = 0 -> 2x = -16 -> x = -8